Online corporate communication: Should national culture matter? - Capece, Guendalina; Di Pillo, Francesca (Frontiers in Communication, 2023)
Introduction The purpose of this paper is to investigate how the culture of a nation influences online corporate communication, focusing on the assessment of the culturability of business websites. Although the Internet constitutes a global phenomenon, cultural filters influence its use at the local level, ultimately determining a more or less favorable attitude toward a given website. Understanding and analysing the cultural adaptation of online communication is crucial as it has the potential to greatly influence how customers perceive and respond to the graphic and content elements. Methods Building upon Hofestede's and Hall's theories, a content analysis technique was used to code the cultural markers and new indicators have been created to allow the association of the graphic elements and the contents of the websites with the cultural characteristics. The countries chosen as case studies are India and Australia, which present significant cultural differences and allow highlighting of the practical implications deriving from the cultural adaptation of the website design. Results The results of this paper show that the company websites analyzed are designed to incorporate the cultural nuances of the target country. In particular, on the Australian websites, there is a greater frequency of cultural markers referring to individualism, masculinity, and uncertainty avoidance compared to Indian ones. On the contrary, Indian websites show more cultural markers referring to power distance, high context, and polychronic characteristics than Australian ones. This paper overcomes the qualitative approaches of the previous literature, developing new indicators for website analysis and providing a quantitative comparison with Hofstede and Hall frameworks. Discussion This work provides a guideline for companies, analysts, and the different professionals involved in online communication and web design. More specifically, they have to be aware of the cultural challenges when they operate outside the national boundaries, by designing a culturally usable website in one of the countries chosen for this study.